(untitled) (Global Journal of Human-Social Science, 2020)
The search for musico-cultural identity and nationalism in Africa as well as in Nigeria gave rise to the evolution of new compositional innovations which stemmed from the use of ethno-compositional materials drawn from such cultures for compositional purposes which are contemporary in structure culturally oriented and globally relevant In response to this search Nigerian Contemporary musicians and Art musicians composers went back as it were to their root giving birth to many contemporary compositions by various contemporary musicians and art musicians in Nigeria and Afr ica including other cultural clime One of such contemporary composition is the musical example titled Ovie for E flat Alto Saxophone and Piano accompaniment In the musicological presentation of Ovie for E flat Alto Saxophone and Piano accompaniment the melodic structure passage of the song texts ovie was used as thematic mater ial to compose an entire work of 173 bars measures Presentation of information pertaining to its pre-compositional consideration and compositional techniques employed in the composition titled ovie was discussed Also literatures were reviewed to buttress facts where necessary From the discussion and analysis of the work it is concluded that compositional materials can be drawn from our cultural and or traditional milieu for vocal music composition instrumental composition or both vocal and instrumental compositions by contemporary music composers